Unclassifiable interstitial lung disease: A review. Issue 1 (9th June 2015) - Skolnik, Kate; Ryerson, Christopher J.
Abstract: Accurate classification of interstitial lung disease (ILD) requires a multidisciplinary approach that incorporates input from an experienced respirologist, chest radiologist and lung pathologist. Despite a thorough multidisciplinary evaluation, up to 15% of ILD patients have unclassifiable ILD and cannot be given a specific diagnosis. The objectives of this review are to discuss the definition and features of unclassifiable ILD, identify the barriers to ILD classification and outline an approach to management of unclassifiable ILD. Several recent studies have described the characteristics of these patients; however, there are inconsistencies in the definition and terminology of unclassifiable ILD due to limited research in this population. Additional studies are required to determine the appropriate evaluation and management of patients with unclassifiable ILD. Abstract : See case report in Respirology Case Reports http://dx.doi.org/10.1002/rcr2.112